2015
DOI: 10.1111/evo.12701
|View full text |Cite
|
Sign up to set email alerts
|

Does evolution lead to maximizing behavior?

Abstract: A long-standing question in biology and economics is whether individual organisms evolve to behave as if they were striving to maximize some goal function. We here formalize this "as if" question in a patch-structured population in which individuals obtain material payoffs from (perhaps very complex multimove) social interactions. These material payoffs determine personal fitness and, ultimately, invasion fitness. We ask whether individuals in uninvadable population states will appear to be maximizing conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 57 publications
1
89
0
Order By: Relevance
“…A number of authors have shown that, for example, in a simple nonadditive two player game, such naïve versions of inclusive fitness wrongly predict the direction of gene frequency change (Grafen ; Queller ; Lehmann et al. ; Okasha and Martens ; Taylor ).…”
Section: The Challenge Of Nonadditivitymentioning
confidence: 99%
See 3 more Smart Citations
“…A number of authors have shown that, for example, in a simple nonadditive two player game, such naïve versions of inclusive fitness wrongly predict the direction of gene frequency change (Grafen ; Queller ; Lehmann et al. ; Okasha and Martens ; Taylor ).…”
Section: The Challenge Of Nonadditivitymentioning
confidence: 99%
“…Several authors (Grafen ; Lehmann et al. ; Okasha and Martens ; Allen and Nowak ; Frank ) have also pointed out that using Hamilton's “neighbor‐modulated fitness” (NMF) resolves this problem in some scenarios (although these authors do not always acknowledge that they are dealing with NMF, instead referring to it by other names, such as “Grafen‐1979 payoff,” which is just NMF in a two player game). This is not surprising as NMF is simply mean number of adult offspring (it adds to the focal individual's fitness the offspring it would receive if its social partners expressed the same phenotype, weighted by the probability that they will, that is, the population frequency of altruism enhanced or diminished by relatedness).…”
Section: The Challenge Of Nonadditivitymentioning
confidence: 99%
See 2 more Smart Citations
“…1 Technically, this expectation is taken over the stationary distribution of the branching process describing the dynamics of a mutant lineage [23]; see Lehmann et al [24] for an example. 2 Up to a transformation with the average reproductive value of the residents [23].…”
Section: Endnotesmentioning
confidence: 99%